2009
DOI: 10.1149/1.3205062
|View full text |Cite
|
Sign up to set email alerts
|

Copper Oxide ALD from a Cu(I) <beta>-Diketonate: Detailed Growth Studies on SiO2 and TaN

Abstract: The atomic layer deposition (ALD) of copper oxide films from [(nBu3P)2Cu(acac)] and wet oxygen on SiO2 and TaN has been studied in detail by spectroscopic ellipsometry and atomic force microscopy. The results suggest island growth on SiO2, along with a strong variation of the optical properties of the films in the early stages of the growth and signs of quantum confinement, typical for nanocrystals. In addition, differences both in growth behavior and film properties appear on dry and wet thermal SiO2. Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…An alternative to NiO x could be an extremely thin layer of CuO x , which has been proposed in several publications. [ 26,33–42 ] A particularly promising result was published by Rao et al [ 26 ] who demonstrated CuO x ‐based MAPI solar cells with an efficiency of 19%. In this work, we therefore investigate CuO x as an alternative to the organic molecule PTAA to better understand the interface‐recombination losses in our devices.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative to NiO x could be an extremely thin layer of CuO x , which has been proposed in several publications. [ 26,33–42 ] A particularly promising result was published by Rao et al [ 26 ] who demonstrated CuO x ‐based MAPI solar cells with an efficiency of 19%. In this work, we therefore investigate CuO x as an alternative to the organic molecule PTAA to better understand the interface‐recombination losses in our devices.…”
Section: Introductionmentioning
confidence: 99%
“…ALD is already being used to deposit high-dielectric metal oxide thin films, and it has also shown great promise for the growth of electrical interconnects between nanometer-sized devices. , As the width of interconnect lines shrink, there is a need to replace aluminum for copper, to lower resistivity and improve electromigration resistance, and current methods for growing copper films require the formation of a seed layer to be able to carry out further electrochemical deposition. , The fact that the seed Cu layer must be grown conformally points to the choice of ALD for this process; however, to date, there are no chemistry-based deposition methods that result in copper films with acceptable adhesion to the surface. Many copper precursors have been designed for CVD and ALD, including compounds with alkoxide, cyclopentadienyl, carboxylate, oxalate, , and acetonate ligands, but most of those require high temperatures, leading to non-self-limiting deposition, possible precursor self-decomposition, and the agglomeration of the deposited copper. New β-ketiminates, β-diketiminates, amino-oxides, and similar N- and/or O-bidentate coordinated compounds have recently been shown to perform better, but their full implementation in ALD processes has still not been accomplished.…”
Section: Introductionmentioning
confidence: 99%
“…media, [15] solar cells, [16] sensors, [17] batteries, [18,19] and catalysis. [20][21][22] For the formation of copper and copper oxides several methods have been applied including electrochemical deposition, [23,24] thermal oxidation of copper, [25] magnetron sputtering, [26] spin-coating, [27][28][29][30][31] chemical beam epitaxy (CBE), [32] atomic layer deposition (ALD) [6,[33][34][35][36][37] and chemical vapor deposition (CVD). [8,10,[38][39][40] For the vacuum-based deposition of copper or copper oxide films the precursors can be classified in two groups: Copper(I) and copper(II) compounds, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For the formation of copper and copper oxides several methods have been applied including electrochemical deposition,, thermal oxidation of copper, magnetron sputtering, spin‐coating, chemical beam epitaxy (CBE), atomic layer deposition (ALD), and chemical vapor deposition (CVD) , , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation